The Influence of Implementing Curriculum Management and Lecturers’ Work Motivation on Improving the Quality of Education - Ginting, Dafid (PPSDP International Journal of Education, 2023)
The purpose of this study was to find out and analyze the magnitude of the influence of Curriculum Management and lecturer work motivation simultaneously on improving the quality of education, to find out and analyze the magnitude of the influence of Curriculum Management partially on improving and to find out and analyze the magnitude of the influence of lecturer work motivation partially on improving the quality of education. In this study the authors used references from the grand theory of administration, middle theory of management and organization and operational theory of curriculum management and work motivation which are still relevant to this research. The research object that was used as the research locus was Polytechnic of Adiguna Maritime Indonesia Medan. Where the population that is used as a sample of respondents is the director and lecturers. The method used is descriptive analysis method with a quantitative approach. The schedule and time of research starts from February 2023 to May 2023. The results showed that dimensions of curriculum management can influence the Improvement of education quality at Polytechnic of Adiguna Maritime Indonesia Medan. It is illustrated that lecturer work motivation has no significant effect on improving the quality of education.